2018
DOI: 10.1016/j.jhsa.2018.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Ideal Starting Point and Trajectory of a Screw for the Dorsal Approach to Scaphoid Fractures

Abstract: Screw starting point and trajectory for scaphoid fractures may be altered based on fracture type to obtain a long screw that is closer to perpendicular to the fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…Similarly, Kupperman et al posit that screw insertion perpendicular to the fracture is of importance. 15 This study is limited by the fact that only dorsal screw insertion was considered, proximal and distal pole as well as waist fractures were tested, and screw position was defined not as the location of the screw within the scaphoid, but rather as a starting point of insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kupperman et al posit that screw insertion perpendicular to the fracture is of importance. 15 This study is limited by the fact that only dorsal screw insertion was considered, proximal and distal pole as well as waist fractures were tested, and screw position was defined not as the location of the screw within the scaphoid, but rather as a starting point of insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Kupperman et al in 2018 and Faucher et al in 2015 showed that perpendicular fixation of scaphoid fractures allowed the use of shorter screws and better fracture compression. 21,22 Therefore, screw protrusion within the middle segments is of increasing relevance as we deviate from the standard starting point and central placement of screws in scaphoid fracture fixation. Several studies have also recommended radiographic evaluation of the scaphoid using the Billiard view, with the forearm 45 pronated and wrist ulnar deviated.…”
Section: Discussionmentioning
confidence: 99%
“…in 2018 and Faucher et al . in 2015 showed that perpendicular fixation of scaphoid fractures allowed the use of shorter screws and better fracture compression 21,22 . Therefore, screw protrusion within the middle segments is of increasing relevance as we deviate from the standard starting point and central placement of screws in scaphoid fracture fixation.…”
Section: Discussionmentioning
confidence: 99%
“…First, the scaphoid’s longitudinal axis was defined manually, from the proximal to the distal pole of the scaphoid. There was no algorithm to help us calculate it, as there might have been in recent 3D studies (Kupperman et al., 2018; Leventhal et al., 2009; Luria et al., 2015; Ten Berg et al., 2018). This means that our results are not strictly comparable to other studies, since the longitudinal axes used may differ by a few degrees.…”
Section: Discussionmentioning
confidence: 99%